PENGARUH MEDIA SOSIAL MARKETING INSTAGRAM DAN BRAND IDENTITY TERHADAP KEPUTUSAN BERKUNJUNG KE SYNCHRONIZE FESTIVAL - Khairul Aditiya Kurniadi, (2023)
Synchronize Festival is a music festival from Indonesia that has been continuously developing since 2016 until now. The presence of innovation by Synchronize Festival led them to continue to increase the number of visitors each year. This study works with Synchronize Festival visitor respondents who had visited at least once. This study uses a quantitative method to determine and analyze the influence of Instagram social media marketing and brand identity on the decision to visit the Synchronize Festival. The sample used in this study is 100 respondents who live in DKI Jakarta. The data collection used a purposive sampling method, and then it was analyzed with descriptive and inferential analysis techniques using the SmartPLS 3.0 application. The results of this study then show that: (1) social media marketing Instagram has a positive and significant effect on visiting decisions (2) brand identity has a positive and significant effect on visiting decisions.